PREFERENSI PETANI TERHADAP KARAKTERISTIK PADI VARIETAS UNGGUL DI DESA KENDAWA JATIBARANG BREBES - Nursidik, Mohamad; Rajiman; Tri Wibowo, Haris (Universitas Muhadi Setiabudi, 2023)
This study aims to determine farmers' preferences for the characteristics of high-yielding rice varieties. The study was carried out from October 2022 – February 2023 in Kendawa Village, Jatibarang District, Brebes Regency. This type of descriptive study uses a survey method, namely collecting data from respondents with a questionnaire. How to determine the sample using proportional random sampling with the slovin formula, the selected sample is 39 respondents. The data analysis method used is the distribution of frequency tables. The results of the study showed that most respondents had a preference for high yielding rice varieties that were resistant to pests and diseases 97%, the appearance of clear white rice 92%, medium plant height 89%, the early maturity of the plant (105-125 DAP) 80%, the number of grains per panicle was 64% more. medium fertilization dose with high absorption 56%, unbalanced fertilization wind factor, water management and planted variety 56%, number of tillers per clump and number of seeds per planting hole, amount of fertilizer used 49% and rice flavor 41%. The distribution of superior varieties in Kendawa Village according to the first planting season of the Inpari 32 variety was 44%, 10% ciherang variety, 2% mekongga variety and 44% IR64 variety. Whereas in the growing season of the two Inpari 32 varieties it was 49%, mekongga 13%, situbagendit 8%, ciherang 5% and IR64 variety 25%.